De quervain tenosynovitis is an atypical presentation of Graves’ disease - Pradhan, Ajit Kumar; Giri, Priyanka; Sahu, Santosh Kumar (Indian Journal of Case Reports, 2026)
De Quervain tenosynovitis is a commonly found wrist pain in women, usually occurring due to autoimmune diseases, overuse, infections and trauma. In Graves’ disease, antibodies stimulate the thyroid gland, leading to diffuse enlargement of the thyroid gland and hypersecretion of thyroid hormones. The association between de Quervain tenosynovitis and Graves’ disease is rarely discussed in the literature. We present the case of a 57-year-old female patient with Graves’ disease with an uncommon initial feature and de Quervain tenosynovitis, before the manifestation of traditional symptoms, which delayed the diagnosis and treatment plan.